A reforma da educação profissional dos anos 1990 e sua aplicação no currículo do centro federal de educação tecnológica do Rio Grande do Norte - Lima, Ana Paula Marinho de (2020)
In this dissertation, we discuss the impacts of the Reform of Professional Education in the 1990s, at the Federal Center for Technological Education of Rio Grande do Norte (CEFET/RN). We seek to answer the following question: how was the Professional Education Reform of the 1990s applied in the curriculum of the CEFET/RN? Therefore, the general objective was to analyze the implications of Reform of Professional Education in the 1990s in the curricular proposal of CEFET-RN. The used methodology was the bibliographical and documentary research. In the bibliographic research, we consulted authors such as: Frigotto (2006), Frigotto and Ciavatta (2003, 2012), Oliveira (2003), Saviani (2011), Ramos (2007), Bresser-Pereira (1997, 1996), Cunha (2005), Shiroma, Moraes and Evangelista (2011), Harvey (2008), Mèszáros (2008) e Harvey (2008). In the documentary research, we carried out an examination of the legislation created by the Ministry of Education during the period of the Professional Education Reform, namely: Decree No. 2,208/1997, Ordinance No. 646/1997, Ordinance No. 1005/1997, Opinion CNE/CEB No. 16/1999 and the Resolution CNE/CEB No. 04/1999. We also analyzed documents elaborated by CEFET-RN: the ETFRN Curricular Proposal (1995) and the Curricular Restructuring Project of the Federal Center for Technological Education of Rio Grande do Norte - volumes I and II (1999). The research is a qualitative one and had as a criterion of analysis the cultural, social and political context in which the documents were prepared, as well as the used theoretical basis. The results showed that before the Reformation CEFET/RN already had a Curriculum Proposal in action, which included in its content the articulation between general and technical disciplines. The training for the subjects was based on the historical-critical conception and on the omnilaterality. With the implementation of the Reform, the institution had to adapt the curriculum to the provisions of Decree No. 2,208 / 1997 and of the Professional Education Expansion Program (PROEP). In this way, CEFET/RN started offering modular and flexible courses. The pedagogical conception, in turn, started to privilege the pedagogy of competences